Clinical characteristics and outcomes in patients with acute myeloid leukemia with concurrent FLT3‐ITD and IDH mutations. Issue 3 (29th October 2020) - Shoukier, Mahran; Kadia, Tapan; Konopleva, Marina; Alotaibi, Ahmad S.; Alfayez, Mansour; Loghavi, Sanam; Patel, Keyur P.; Kanagal‐Shamanna, Rashmi; Cortes, Jorge; Samra, Bachar; Jabbour, Elias; Garcia‐Manero, Guillermo; et al.
Abstract : Background: Isocitrate dehydrogenase ( IDH1 and IDH2 ) mutations commonly co‐occur with FMS‐like tyrosine kinase 3 ( FLT3 ) mutations in patients with acute myeloid leukemia (AML). Methods: The authors reviewed cases of patients with FLT3 ‐internal tandem duplication ( FLT3 ‐ITD)–mutated AML with concurrent IDH mutations diagnosed between January 2011 and December 2018. Results: A total of 91 patients with FLT3 ‐ITD and IDH1 or IDH2 "double‐mutated" AML were identified; 36 patients had concurrent FLT3 ‐ITD/ IDH1 mutations (18 in the frontline and 18 in the recurrent and/or refractory [R/R] setting) and 55 patients had concurrent FLT3 ‐ITD/ IDH2 mutations (37 in the frontline and 18 in the R/R setting). FLT3 and/or IDH inhibitors ( FLT3 Is and/or IDH Is) were given as a single agent or in combination with cytotoxic chemotherapy (CCT) or low‐intensity therapy (LIT). Rates of complete remission (CR) plus CR with incomplete count recovery (CRi) with the use of CCT and FLT3 Is were 100% and 64%, respectively, in patients in the frontline and R/R settings. CCT with IDH Is was given in 2 frontline patients and both achieved a CR. LIT with FLT3 Is in the frontline and R/R settings demonstrated CR and CRi rates of 67% and 28%, respectively. Single‐agent FLT3 Is and IDH Is demonstrated limited activity with a CR and/or CRi rate of 14% in patients with disease in the R/R setting. Conclusions: The combination of FLT3 I‐based therapy with CCT or LIT appeared to be effective in both the frontline and R/R settings among patients with FLT3 ‐ITD/ IDH co‐mutated disease. Fewer patients with double‐mutated disease received CCT or LIT with IDH1/2 inhibitor in the frontline setting; however, high response rates also were noted with this approach. Lay Summary: The prognostic influence of FMS‐like tyrosine kinase 3–internal tandem duplication ( FLT3 ‐ITD) and isocitrate dehydrogenase ( IDH ) co‐mutation status on outcomes in patients with acute myeloid leukemia receiving an FLT3 inhibitor, non– FLT3 / IDH inhibitor–based regimens, or an IDH inhibitor is unclear. This is an important clinical question because multiple targeted therapies for FLT3 and IDH1/2 mutations have become available. The results of the current study demonstrated that a combination of a FLT3 inhibitor with cytotoxic chemotherapy or low‐intensity therapy appears to be an effective approach in patients with FLT3 ‐ITD/ IDH co‐mutated disease in both the frontline and recurrent and/or refractory settings. Fewer dual‐mutated patients received cytotoxic chemotherapy or low‐intensity therapy with an IDH1/2 inhibitor in the frontline setting; however, excellent responses also were observed with this approach. Abstract : The combination of FMS‐like tyrosine kinase 3 ( FLT3 ) inhibitor–based therapy with high‐intensity and/or intermediate‐intensity conventional cytotoxic chemotherapy or low‐intensity regimens appears to be effective in patients with FLT3 –internal tandem duplication ( FLT3‐ ITD) and/or isocitrate dehydrogenase ( IDH ) ( FLT3 ‐ITD/ IDH ) co‐mutated acute myeloid leukemia in both the frontline and recurrent and/or refractory settings. Patients with FLT3 ‐ITD/ IDH2 acute myeloid leukemia generally are younger and their disease is associated with improved overall survival compared with patients with FLT3 ‐ITD/ IDH1 –mutated disease in both the frontline and recurrent and/or refractory settings.